Systemic medical complications following total ankle arthroplasty: A review of the evidence. Issue 7 (October 2022) - Curlewis, Keegan; Leung, Brook; Sinclair, Lucy; Chan, Gareth; Bendall, Stephen; Ricketts, David
Abstract: Background: Total Ankle Arthroplasty (TAA) is increasingly undertaken for the treatment of end-stage ankle arthritis. For each TAA procedure informed consent is required. The consent process should include discussion of the relevant complications, both systemic and regional. There is a lack of data regarding the systemic complications of TAA. This might cause problems in obtaining valid informed consent. Methods: We reviewed and summarised the literature regarding the systemic complications and mortality rate of TAA. Results: The average rate of systemic medical complications after TAA was 3% (range: 0–7%). The average mortality rate following TAA was 0.3% (range: 0–0.72%). The following were risk factors for systemic medical complications: obesity, diabetes, systemic co-morbidities, preoperative blood transfusion, revision procedures, and long anaesthetic duration. Conclusions: When obtaining informed consent for TAA a systemic complication rate of 3% and a mortality rate of 0.3% ought to be included and documented.